The Analysis of Errors Made by The Third Year Students of English Department in Translating Narrative Text - Vioksana Bonita Adelia; Rusdi Noor Rosa (Universitas Negeri Padang, 2020)
This study aims at finding out the errors made by the third year English Department students of Universitas Negeri Padang in translating a narrative text from English into bahasa Indonesia. This study used a descriptive method. The data were the translation of the narrative text entitled Snow White done by the third year English Department students of Universitas Negeri Padang. The data were collected using a test and were analyzed using the error analysis. The results of the study indicate semantic error is the error frequently committed by the students in their translation with the frequency of 72 times (59%). Pragmatic error (29%) is the second most frequent error, while morphological error and syntactical error are seldom found in the students’ translation. In conclusion, the errors made by the students are mainly motivated by their tendency to follow the meaning of the dictionary (word for word translation).